2009
DOI: 10.1007/s11999-008-0465-3
|View full text |Cite
|
Sign up to set email alerts
|

Resurfacing is Comparable to Total Hip Arthroplasty at Short-term Followup

Abstract: Metal-on-metal total hip resurfacing arthroplasty has had excellent reported results at early to midterm followup, and some studies suggest that outcomes are comparable to conventional THA. We compared the clinical and radiographic outcomes of two closely matched groups of 54 patients who underwent resurfacing and conventional THA, respectively. Each group consisted of 36 men and 18 women who had a mean age of 52 years and a mean body mass index of 29 kg/m 2 . At a minimum followup of 24 months (mean, 40 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
61
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(66 citation statements)
references
References 18 publications
5
61
0
Order By: Relevance
“…Fowble et al [14], however, pointed out patients who undergo SRA have characteristics different from those of patients who undergo THA, including a higher preoperative UCLA activity score, which was associated with higher function and a higher postoperative UCLA activity score but also a higher incidence of slight or mild pain. These differences in pre-and postoperative activity scores between patients receiving SRA and THA have also been reported by Vail et al [39] and Mont et al [30]. This is an example of the difficulty in comparing results of SRA with THA.…”
Section: Introductionsupporting
confidence: 66%
See 2 more Smart Citations
“…Fowble et al [14], however, pointed out patients who undergo SRA have characteristics different from those of patients who undergo THA, including a higher preoperative UCLA activity score, which was associated with higher function and a higher postoperative UCLA activity score but also a higher incidence of slight or mild pain. These differences in pre-and postoperative activity scores between patients receiving SRA and THA have also been reported by Vail et al [39] and Mont et al [30]. This is an example of the difficulty in comparing results of SRA with THA.…”
Section: Introductionsupporting
confidence: 66%
“…There are a number of potential advantages suggested but not proven for SRA over THA, including clinical advantages such as return to higher activity levels and less activity-related thigh pain and fewer complications with postoperative limb length discrepancy and limp (Table 5) [14,15,21,26,27,30,39,40]. Given the high survivorship and low complication rate of THA [23], SRA must demonstrate a similar complication rate in addition to some clinical advantage to warrant continued use of this procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional outcomes and quality of life following HRA Patients treated with HRA have been noted to have high postoperative activity levels and quality of life scores (Narvani et al, 2006;Naal et al, 2007), which are higher than those of their THA counterparts (Pollard et al, 2006;Vail et al, 2006;Lavigne et al, 2008a;Mont et al, 2009) -even after adjustments for pre-operative activity levels (Zywiel et al, 2009). One study reported that more HRA patients returned to work (96%) and heavy to moderate activities (72%) 1 year postoperatively than THA patients (66% and 39%, resp.).…”
Section: Cementing Techniquementioning
confidence: 99%
“…It was reported that the symptom of hip OA occurs in 3% of the elderly 8) . In general, older patients with hip OA undergo THA for the reduction of pain, and the results of THA are excellent 9,10) . THA permits full weight bearing during the early postoperative period.…”
Section: Introductionmentioning
confidence: 99%